Paleopolyploidies and Genomic Fractionation in Major Eudicot Clades - Teng, Jia; Wang, Jianyu; Zhang, Lan; Wei, Chendan; Shen, Shaoqi; Xiao, Qimeng; Yue, Yuanshuai; Hao, Yanan; Ge, Weina; Wang, Jinpeng (Frontiers in Plant Science, 2022)
Eudicots account for ~75% of living angiosperms, containing important food and energy crops. Recently, high-quality genome sequences of several eudicots including Aquilegia coerulea and Nelumbo nucifera have become available, providing an opportunity to investigate the early evolutionary characteristics of eudicots. We performed genomic hierarchical and event-related alignments to infer homology within and between representative species of eudicots. The results provide strong evidence for multiple independent polyploidization events during the early diversification of eudicots, three of which are likely to be allo-polyploidies: The core eudicot-common hexaploidy (ECH), Nelumbo-specific tetraploidy (NST), and Ranunculales-common tetraploidy (RCT). Using different genomes as references, we constructed genomic alignment to list the orthologous and paralogous genes produced by polyploidization and speciation. This could provide a fundamental framework for studying other eudicot genomes and gene(s) evolution. Further, we revealed significantly divergent evolutionary rates among these species. By performing evolutionary rate correction, we dated RCT to be ~118-134 million years ago (Mya), after Ranunculales diverged with core eudicots at ~123-139 Mya. Moreover, we characterized genomic fractionation resulting from gene loss and retention after polyploidizations. Notably, we revealed a high degree of divergence between subgenomes. In particular, synonymous nucleotide substitutions at synonymous sites (Ks) and phylogenomic analyses, implied that A. coerulea might provide the subgenome(s) for the gamma-hexaploid hybridization.